Field and greenhouse application of an attract‐and‐kill formulation based on the yeast Hanseniaspora uvarum and the insecticide spinosad to control Drosophila suzukii in grapes. Issue 3 (15th December 2021) - Spitaler, Urban; Cossu, Carlo S; Delle Donne, Lorenz; Bianchi, Flavia; Rehermann, Guillermo; Eisenstecken, Daniela; Castellan, Irene; Duménil, Claire; Angeli, Sergio; Robatscher, Peter; Becher, Paul G; Koschier, Elisabeth H; et al.
Abstract: BACKGROUND: The invasive insect Drosophila suzukii (Matsumura) is an important pest of several red grape varieties. The yeast Hanseniaspora uvarum (Niehaus), which is associated with D. suzukii, strongly attracts flies and stimulates them to feed on yeast‐laden food. In the present study, a formulation based on H. uvarum culture with spinosad insecticide was applied to the foliage of vineyards and control of D. suzukii was compared to applying spinosad to the whole plant. After successful H. uvarum and insecticide application in the vineyard, we tested additional H. uvarum ‐based formulations with spinosad in a greenhouse to determine their capacity to control D. suzukii . RESULTS: Application of the H. uvarum ‐spinosad formulation at 36.4 g of spinosad per hectare reduced the D. suzukii field infestation at the same rate as applying 120 g of spinosad per hectare and prevented spinosad residues on grapes. Leaves treated with H. uvarum and spinosad in the field and transferred to a laboratory assay caused high mortality to flies and reduced the number of eggs laid on fruits. Formulations with spinosad applied in the greenhouse showed that both H. uvarum culture and the yeast cell‐free supernatant of a centrifuged culture increased fly mortality and reduced the number of eggs laid compared to the unsprayed control. CONCLUSION: In comparison to typical spinosad spray applications, the use of H. uvarum in combination with spinosad as an attract‐and‐kill formulation against D. suzukii reduces pesticide residues on the fruits by targeting the treatment to the canopy and decreasing the amount of insecticide per hectare without compromising control efficacy. Abstract : Application of the yeast Hanseniaspora uvarum in a control strategy against Drosophila suzukii reduces insecticide residues on grapes by targeting the canopy, which does not compromise the control efficacy. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.